Evaluation of the genetic toxicity of synthetic chemicals (XIV)-in vitro chromosomal aberration assay with 11 chemicals in Chinese hamster lung cells - Kim, Youn-Jung; Ryu, Jae-Chun (KOREAN SOCIETY TOXICOGENOMICS & TOXICOPROTEOMICS-KSTT, 2006)
The detection of many synthetic chemicals used in industry that may pose a genetic hazard in our environment is of great concern at present. Since these substances are not limited to the original products, and enter the environment, they have become widespread environmental pollutants, thus leading to a variety of chemicals that possibly threaten the public health. In this respect, to regulate and to evaluate the chemical hazard will be important to environment and human health. The clastogenicity of 11 synthetic chemicals was evaluated in Chinese hamster lung fibroblast cells in vitro. 1-Chloro-3-bromopropane CAS No. 109-70-6) induced chromosomal aberrations with significance at the concentration of 185.0 mu g/mL and 1,600 mu g/mL both in the presence and absence of metabolic activation system, respectively. Triphenyl phosphite (CAS No. 101-02-0), which is one of the most cytotoxic chemical among 11 chemicals tested revealed no clastogenicity in the range of 95.0-4.9 mu g/mL both in the presence and absence of metabolic activation system. From the results of chromosomal aberration assay with 11 synthetic chemicals in Chinese hamster lung cells in vitro, 1-chloro-3-bromopropane revealed a positive clastogenic result in this study.
Keywords: PERIPHERAL-BLOOD RETICULOCYTES; MICRONUCLEUS ASSAY; MUTATION SPECTRUM; SOS CHROMOTEST; CARCINOGENS; MUTAGENS; LINE; DI(2-ETHYLHEXYL)PHTHALATE; GENOTOXICITY; EXPOSURE